A Systematic Literature Review of Cross-Cultural Studies on Interior Perception - Ayşen Özkan; Türkan Sultan Yaşar Ismail (PLANARCH - Design and Planning Research)
Individuals, as the fundamental building blocks of societies, engage in a continuous and evolving relationship with their environments, fostering unique cognitive patterns within their cultures. Factors like geography, climate, historical events, and social dispositions can lead to differences in cultural perceptions across different regions. On the other hand, spaces reflect ways of life and cultural values. Individuals’ perceptions and behaviours within their surroundings may differ depending on the cultures they belong to. Environmental studies within cultural contexts have been of interest in the architecture and psychology fields. There has been a notable increase in research interest in cross-cultural spatial perception. However, the studies mostly focus on the scale of architecture or landscape design. Interior spaces can be seen as one of the main surroundings for people, especially in the context of the current century urban context we live in. Therefore, it is essential to understand the differences in cultural perceptions of space to promote inclusivity within the global cultural context. This study aims to examine the similarities and differences between interior perception studies from a cross-cultural perspective. The systematic literature mapping method with inclusion and exclusion criteria was used within the Scopus database, and in total, 26 relevant perception studies focusing on cultural variation were selected and analyzed according to different interior typologies and countries. The findings indicate that individuals from diverse cultural backgrounds respond differently to various spatial typologies and interior spaces, with these differences linked to factors such as space programming, color choices, and levels of privacy.